Physiological and pathophysiological actions of insulin in the liver - Naoto Kubota; Tetsuya Kubota; Takashi Kadowaki (Endocrine Journal)
The liver plays an important role in the control of glucose homeostasis. When insulin levels are low, such as in the fasting state, gluconeogenesis and glycogenolysis are stimulated to maintain the blood glucose levels. Conversely, in the presence of increased insulin levels, such as after a meal, synthesis of glycogen and lipid occurs to maintain the blood glucose levels within normal range. Insulin receptor signaling regulates glycogenesis, gluconeogenesis and lipogenesis through downstream pathways such as the insulin receptor substrate (IRS)-phosphoinositide 3 (PI3) kinase-Akt pathway. IRS-1 and IRS-2 are abundantly expressed in the liver and are thought to be responsible for transmitting the insulin signal from the insulin receptor to the intracellular effectors involved in the regulation of glucose and lipid homeostasis. Impaired insulin receptor signaling can cause hepatic insulin resistance and lead to type 2 diabetes. In the present study, we focus on a concept called “selective insulin resistance,” which has received increasing attention recently: the frequent coexistence of hyperglycemia and hepatic steatosis in people with type 2 diabetes and obesity suggests that it is possible for the insulin signaling regulating gluconeogenesis to be impaired even while that regulating lipogenesis is preserved, suggestive of selective insulin resistance. In this review, we review the progress in research on the insulin actions and insulin signaling in the liver.